Natural Fibre Connect 2025: Global Industry Unites in Edinburgh to Advance Collaboration, Climate Action and Regenerative Futures - Sustainable Fibre Alliance (Sustainable Fibre Alliance, 2025)
A press release on the Natural Fibre Connect 2025 conference describing main presentations and outcomes, and to which ILRI contributed through the project STELARR (Sustainable Large-Scale Investments for Rangeland Restoration).